Pemetaan Potensi Desa Ngestirejo - Kristiawan, Yanuarius Benny (Jurnal Atma Inovasia, 2021)
The village potential mapping was carried out in Ngestirejo Village, Gunungkidul Regency which was selected in accordance with the decision of the Institute for Research and Community Service (LPPM) Atma Jaya University Yogyakarta (UAJY). The purpose of this paper is to see and describe the potential that exists in Ngestirejo Village that can be developed by the local community which can be found through various sources on the internet and written works of other sources. Ngestirejo Village has several village potentials that can be developed, such as in the tourism sector, which consists of natural and cultural tourism and agriculture.